A Review of Randomized Controlled Trials in Cleft and Craniofacial Surgery. Issue 2 (March 2018) - Bekisz, Jonathan M.; Fryml, Elise; Flores, Roberto L.
Abstract : Abstract: This study presents a systematic review of randomized controlled trials (RCTs) in cleft and craniofacial surgery. All studies reporting on RCTs in cleft and craniofacial surgery were identified on PubMed using the search terms "cleft, " "velopharyngeal insufficiency, " "velopharyngeal dysfunction, " "nasoalveolar molding, " "gingivoperiosteoplasty, " "Pierre Robin sequence, " "craniofacial, " "craniosynostosis, " "craniofacial microsomia, " "hemifacial microsomia, " "hypertelorism, " "Le Fort, " "monobloc, " "distraction osteogenesis, " "Treacher Collins, " and "Goldenhar." Studies were excluded if they were not randomized, did not focus primarily on topics related to cleft or craniofacial surgery, included repeat publications of data, or were unavailable in English. Studies were evaluated on demographic and bibliometric data, study size, specific area of focus, and findings reported. Four hundred forty-seven unique studies were identified. One hundred eighty-three papers met inclusion criteria (115 cleft lip and palate, 65 craniofacial, and 3 spanning both disciplines). Sixty-six (36%) were dedicated to topics related to surgical techniques. There were no studies comparing current cleft lip or soft palate repair techniques and no studies on cleft rhinoplasty. The most frequently reported surgical topic was cleft palate. There were several studies on orthognathic techniques which compared distraction osteogenesis to traditional advancement. Most craniofacial operations, such as cranial vault remodeling and frontofacial advancement/distraction, were not represented. Several standard operations in cleft and craniofacial surgery are not supported by Level I evidence from randomized controlled trials. Our community should consider methods by which more RCTs can be performed, or redefine the acceptable standards of evidence to guide our clinical decisions.